Age estimation using pulp tooth area ratio in North Indian population - Munish Kumar; Sweta Choudhary (Wolters Kluwer Medknow Publications, 2019)
Introduction: One of the most common dental expert advice asked by the law enforcing agencies is to provide identity and age of the accused or person involved. Age determination is done for various causes including that of dead bodies for reasons as unlawful cases and also in badly disfigured bodies in disasters, such as natural calamities or manmade like fires, accidents, etc., In living individual, the age estimation is done to crosscheck whether an individual has attained the age for lawful liability when records are not available or suspected. Materials and Methods: Study was done on 300 individuals (150 males-females each) using RVG of Right maxillary canine and data is processed by AutoCAD 2006. Results: Intraclass correlation coefficients (r) for reliability of predicted age calculated have significant P value (<0.05). Discussion: The purpose of this study was to validate the Modified Cameriere's method of age estimation using pulp tooth area ratio given by Jeevan et al. on North Indian population. Conclusion: We can conclude from this study that AutoCAD is definitely a tool for measurements of pulp/tooth area ratio which can further be used for age estimation in forensic odontology; Gender has no significant influence on age estimation..